Discourse on strikes: Journalistic approach to the “Law to Regulate Strikes” (n. 21.049)) by La Nación: September 2019-January 2020 - Quesada-Webb, Armando (2023)
Mass media outlets have political agendas and, for that reason, how they approach specific subjects has the purpose of influencing the receptor's opinion. Taking that reasoning as a starting point, this document analyzed how a Costarican media, newspaper La Nación, approached the subject of the discussion and later approval of the bill of law no. 21. 049, best known as the “Law to Regulate Strikes.” The research was focused on understanding how this media elaborated its narrative and manifested its ideological stand throughout the journalistic coverage of this bill of law. To achieve this, both the content and framing of a selection of publications by the media regarding this subject were analyzed. The results exposed how La Nación elaborated a discourse characterized by the utilization of a tendentious vocabulary, that highlighted the necessity of approving this law by its association with the maintenance of public order, and also constructed an ideological enemy through generalization and minimization of the opposition’s voices. This confirms that La Nación carried out a biased coverage that empowered the political figures who promoted this bill of law and weakened those who opposed it.